Recurrent glioblastoma in national guidelines on the diagnosis and treatment of gliomas: A matter of European practice variation - Mark P. van Opijnen; Rob J.A. Nabuurs; Filip Y.F. de Vos; Mohini T.R. Ramsoedh; Joost J.C. Verhoeff; Marjolein Geurts; Marike L.D. Broekman (Brain and Spine)
Introduction: The optimal treatment for recurrent glioblastoma patients remains not well-defined in international guidelines. On top of that, the availability of national guidelines is uncharted. Research question: This study aimed to investigate the availability of national guidelines on the diagnosis and treatment of adult glioma throughout Europe, specifically focusing on recurrent glioblastoma. Material and methods: Medical specialists with neuro-oncology expertise from all European countries were asked for the availability of official national guidelines. The primary outcome was whether guidelines provided recommendations on the treatment of recurrent glioblastoma in adults. Secondary outcomes included treatment specific recommendations and the role of clinical trials in the treatment of recurrent glioblastoma. The quality of the guidelines was assessed using the AGREE II instrument. Results: Of the 50 countries in Europe, information on guideline availability was obtained for 38 countries (76%). In twelve countries (24%) national guidelines on the diagnosis and treatment of glioma in adults exist. Focusing on recurrent glioblastoma, nine (18%) of the European countries provided any recommendations on the treatment of recurrent glioblastoma. In four (33%) guidelines it was explicitly stressed that there is currently no standard or evidence-based treatment for these patients. Discussion and conclusion: National guidelines on the treatment of glioblastoma in adults are not uniformly available in Europe. In addition, and in contrast with international guidelines, the national guidelines differ profoundly in their recommendations regarding recurrent glioblastoma. This could contribute to unwanted practice variation. Efforts are needed to not only optimize, but also harmonize treatment for recurrent glioblastoma patients.